The Influence of Product Reviews and Content Creators on Purchase Interest through Affiliate Marketing of Shopee E-Commerce users in Kudus Regency - Kholifatul Maulida; Mochamad Edris; Joko Utomo (Journal of Finance and Business Digital, 2023)
This research aims to test the influence of product reviews and content creators on purchasing interest through affiliate marketing of Shopee e-commerce users in Kudus Regency. This type of quantitative research, with a sample size of 156 respondents. Data collection uses a questionnaire. Data analysis includes validity and reliability tests, data analysis using SEM AMOS version 23. The results of the research directly product reviews have a significant positive effect on affiliate marketing. Content Creator has a significant positive effect on Affiliate Marketing. Product reviews have an insignificant positive effect on purchasing interest. Content Creator has an insignificant positive effect on purchasing interest. Affiliate marketing has a significant positive effect on Purchase Interest. The results of the intervening test show that the affiliate marketing variable is able to act as an intervening variable between product reviews and content creators on the buying interest of Shopee e-commerce users in Kudus Regency